Pengaruh Book Tax Differences dan Struktur Kepemilikan Saham terhadap Persistensi Laba - Mu'arofah, Endah Lailatul; Ulum, Ihyaul; Harventy, Gina (Jurnal Reviu Akuntansi dan Keuangan)
The aim of this study is to get empirical evidence about the influence of book tax differences (BTD) and managerial ownership to earnings persistence. BTD is separated into normal BTD and abnormal BTD, and classified into positive BTD and negative BTD. There are four components that are tested in BTD, namely large positive abnormal BTD (LPABTD), large negative abnormal BTD (LNABTD), large positive normal BTD (LPNBTD), and large negative normal BTD (LNNBTD). The ownership structure that tested is managerial ownership. This research uses multiple linear regression analysis with population of manufacturing companies in Indonesia Stock Exchange. The result shows that companies with LPABTD, LNABTD, and LPNBTD have higher earnings persistence than companies without the components. Conversely, companies with LNNBTD have lower earnings persistence than companies without the components. The structure of managerial stock ownership increases the earnings persistence unless the companies have large negative normal BTD. Key words: book tax differences, earnings persistence, managerial ownership, tax planning